Marine CFD 2011 : 22-23 March, 2011, London, UK, papers (Royal Institution of Naval Architects, 2011)
Computational Fluid Dynamics (CFD) is now used to solve a wide range of maritime applications from resistance prediction to slamming loads calculation. While it may still lack the accuracy to match results obtained in real-life experiments, it can provide important insights into physical flow characteristics and offers an economic way to investigate a range of design options.